Results of eye lens doses control of medical personnel in St. Petersburg - Ekaterina N. Shleenkova; Vladislav Yu. Golikov; Georgy N. Kaidanovsky; Stepan Yu. Bazhin; Vladimir A. Ilyin (Радиационная гигиена)
Results of individual monitoring for personnel of X-ray surgical teams in several clinics of St. Petersburg are presented and analyzed. Measurements of the operational quantities – individual dose equivalents Hp (3) and Hp (10) were performed by thermoluminescent dosimetry method. Dosimeters designed to measure Hp (3) were located in the operators forehead area, and to determine Hp (10) both above the operator ‘s individual protective apron in the collar or chest area and under the protective apron in the chest area. The results of 34 measurements of the annual values of Hp (3) and Hp (10) measured above the apron and 24 values of Hp (10) measured below the apron were processed and analyzed. The results after the statistical treatment show that the probability of exceeding the annual values of Hp (3) in the personnel of X-ray surgical teams of the new dose limit 20 mSv is small, less than 1%. Exceeding the current dose limit of the equivalent exposure dose of the lens of the eye (150 mSv) is hardly possible at all under normal conditions. The best solution for evaluating the radiation dose of the lens of the eye is to measure the individual equivalent of the dose Hp (3), using a suitably calibrated TL-dosimeter (thermoluminescent dosimeter) located near the worker’s eyes. However, this additional dosimeter is only necessary when the values of eye lens equivalent dose can approach the new value of dose limit of 20 mSv. According to the results of the study, it is possible to introduce such an additional dosimeter if the annual value of Hp (10) recorded by the dosimeter located above the protective apron is more than 10 mSv.